Clinical utility of fetal autopsy and its impact on genetic counseling. (5th April 2015) - Nayak, Shalini S.; Shukla, Anju; Lewis, Leslie; Kadavigere, Rajagopal; Mathew, Mary; Adiga, Prashanth K.; Vasudeva, Akhila; Kumar, Pratap; Shetty, Jyothi; Shah, Hitesh; Girisha, Katta M.
Abstract Objectives We aimed to analyze the utility of fetal autopsy in terms of its contribution to establishing a definitive diagnosis and its impact on genetic counseling. Subjects and methods Detailed fetal autopsy was carried out in fetuses referred for examination. Clinical utility of fetal autopsy and its impact on counseling were measured by adapting previously published parameters. Results We performed autopsy in 230 fetuses. There were 106 cases with single system and 92 cases with multisystem involvement. We confirmed prenatal findings in 23% of cases and observed additional findings in 37% of cases. In 23% of cases, autopsy findings differed enough to change the diagnosis. However, in 17% of fetuses, no cause of fetal loss was determined. Risk of recurrence became clear in 30.3% of the fetuses, and risk remained the same, but the diagnosis was different in 4.8% of cases after autopsy. Hence, autopsy led to refinement of the risk of recurrence in 36% of cases. Autopsy aided prenatal counseling of couples in 77% of cases by either confirming the prenatal findings (35%) or providing new information/ruling out a diagnosis (42%). Conclusion The present study quantifies the utility of fetal autopsy in reproductive genetic counseling in a large cohort. © 2015 John Wiley & Sons, Ltd.